Communication Styles of Primary School Teachers During Teaching - Stavropoulou, Eleni; Stamatis, Panagiotis J. (International Journal of Criminology and Sociology, 2017)
In international literature, teacher communication style (TCS) is defined as the teacher's ability to effectively communicate, verbally and nonverbally, with his/her students in order to improve their academic performance and manage their behavior. Surveys in educational environments show that each teacher may display a primary communication style during classroom teaching with recurring other styles of communication, which can change according to the audience and the situations he/she has to deal with. This combination of communication styles enables individuals not to feel confined to the way they communicate, but to become flexible and capable of choosing communication strategies according to the variety of situations they are faced with. Within this framework, the present study deals with the phenomenon of human communication and focuses on the communication style of teachers. More specifically, the study explores the communication style of primary school teachers during teaching process, utilizing modern Greek and international typology and teachers’ communication strategies according to Jay Lemke and behaviors related to verbal and nonverbal immediacy during teaching. Those communication styles shaping the school climate and contribute in interpersonal relationship development among teachers, students and parents.